The persistence of regional new business formation-activity over time: assessing the potential of policy promotion programs - Michael Fritsch; Pamela Mueller (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2005)
We investigate regional differences in the level and the development of regional new business formation activity. There is a pronounced variance of start-up rates across the regions. The level of regional new firm formation is rather pathdependent so that changes are relatively small. The main factors determining the level of regional start-ups are innovation and entrepreneurship. These factors also seem to be responsible for changes in the level of regional new business formation. In addition, unemployment plays a role. Steering innovation and creating an entrepreneurial atmosphere could be an appropriate starting point for policy measures that try to promote start-ups. Our empirical evidence strongly suggests that such measures may have significant effect only in the long run. – – Wir analysieren regionale Unterschiede des Niveaus von Gründungsaktivitäten und dessen Entwicklung. Die regionalen Gründungsraten weisen eine ausgeprägte Streuung auf. Dabei ist eine deutliche Pfadabhängigkeit der Gründungsaktivitäten feststellbar, so dass Änderungen relativ gering ausfallen. Die wesentlichen Bestimmungsgründe für das Niveau der Gründungsaktivitäten sind Innovation und Unternehmertum. Diese Faktoren spielen auch für Veränderungen der regionalen Gründungsaktivitäten eine Rolle. Zusätzlich hat hier auch das Niveau der regionalen Arbeitslosigkeit einen Einfluss. Die Stimulierung von Innovationsaktivitäten und von Entrepreneurship stellen geeignete Ansatzpunkte für eine Politik dar, die auf eine Steigerung der Gründungsaktivitäten abzielt. Unser empirischer Befund weist allerdings darauf hin, dass ein wesentlicher Effekt solcher Maßnahmen erst längerfristig erwartet werden kann.
Keywords: M13; O1; O18; R11; 330; New businesses; entrepreneurship; growth regimes; time lags; Regionalentwicklung; Unternehmensgründungen; Entrepreneurship; Wachstumsregime; Time Lags; Unternehmensgründung; Region; Zeit; Lag-Modell; Innovationspolitik; Entrepreneurship-Ansatz; Deutschland; Wirtschaftsförderung